PULMONARY AGENESIS-GROUP I WITH UPAA DIAGNOSED IN ELDERLY GERIATRIC AGE - Sharma, Raghav; Upadhyaya, Vidya; Attar, Nazir (Journal of Health and Allied Sciences NU, 2012)
Pulmonary agenesis and UPAA (unilateral pulmonary artery agenesis) is a rare developmental lung defect in which there is complete absence or hypoplasia of one or both lungs. It can be either isolated or associated with other congenital anomalies. The percentage of diagnosis of this condition during life has risen considerably, however it is true that more than 50% of the patients with this condition die in the first year of life. The symptoms and severity of this condition is often variable. Here with we present a male patient with left upper lobe pulmonary agenesis with left unilateral pulmonary artery agenesis (UPAA) which was detected and diagnosed for the first time at the ripe age of 70 years. Here we also review the relevant literature regarding the condition and the radiology including CT scan is described.
Keywords: Pulmonary agenesis; Agenesis of left upper lobe; Unilateral pulmonary artery agenesis-UPAA; Congenital lung malformations; CT chest